Comprehensive insights of Sneddon syndrome: A clinical perspective - Ahmad Yousef Alazzam (Journal of Central Nervous System Disease)
BACKGROUND Sneddon’s syndrome is a rare thrombotic vasculopathy characterized by the coexistence of both cerebrovascular events and livedo reticularis. OBJECTIVE This review aims to raise awareness among physicians by discussing the whole clinical spectrum of the disease. Typically, Sneddon syndrome presents in middle-aged women with a cerebrovascular accident and a preexisting skin rash, which is livedo reticularis. Diagnosis is primarily clinical, relying on a high index of suspicion. Management focuses mainly on reducing the risk of cerebral infarctions and alleviating symptoms. CONCLUSION Further research is necessary to better understand the disease’s nature, which will contribute to improving early diagnosis and optimal management.